Mutated IL-32θ (A94V) inhibits COX2, GM-CSF and CYP1A1 through AhR/ARNT and MAPKs/NF-κB/AP-1 in keratinocytes exposed to PM10 - Jinju Kim; Chae-Min Lim; Nahyun Kim; Hong-Gyum Kim; Jin-Tae Hong; Young Yang; Do-Young Yoon (Scientific Reports)
Abstract Exposure to particulate matter (PM) in the air harms human health. Most studies on particulate matter’s (PM) effects have primarily focused on respiratory and cardiovascular diseases. Recently, IL-32θ, one of the IL-32 isoforms, has been demonstrated to modulate cancer development and inflammatory responses. This study revealed that one-point mutated IL-32θ (A94V) plays an important role in attenuating skin inflammation. IL-32θ (A94V) inhibited PM-induced COX-2, a pro-inflammatory cytokine GM-CSF and CYP1A1 in PM-exposed human keratinocytes HaCaT cells. IL-32θ (A94V) modulating effects were mediated via down-regulating ERK/p38/NF-κB/ AP-1 and AhR/ARNT signaling pathways. Our study indicates that PM triggers skin inflammation by upregulating COX-2, GM-CSF and CYP1A1 expression. IL-32θ (A94V) suppresses the expressions of COX-2, GM-CSF, and CYP1A1 by blocking the nuclear translocation of NF-κB and AP-1, as well as inhibiting the activation of the AhR/ARNT signaling pathway. Our findings offer valuable insights into developing therapeutic strategies and potential drugs to mitigate PM-induced skin inflammation by inhibiting the ERK/p38/NF-κB/AP-1 and AhR/ARNT signaling pathways.